PERANCANGAN PRODUK PERHIASAN MENGGUNAKAN TERAPAN ATUMICS TERHADAP WAYANG PANJI: JEWELRY PRODUCT DESIGN USING ATUMICS APPLICATIONS TO WAYANG PANJI - Gerardus Gladwin Poillot; Krishna Hutama; Yan Yan Sunarya (Jurnal Seni dan Reka Rancang: Jurnal Ilmiah Magister Desain, 2024)
The issue raised in this research is related to how some Indonesian cultures are starting to be forgotten by the younger generation. With the following issues it can be seen that the problem that arises is one of the Indonesian cultures such as wayang panji which is starting to receive less appreciation from Indonesian society so that the goals to be achieved in the research This is designing jewelry as an effort to preserve Indonesia's original culture, namely wayang panji. The method used in the research is a qualitative method combined with the ATUMICS method, which is used to look at elements that can be maintained and transformed in a culture, especially wayang panji. The result obtained is a jewelry product design in the form of earrings, bracelets and also necklaces with inspiration taken based on the shape of the wayang panji irah-irahan where the wayang panji irah-irahan is one of the characteristics of wayang panji and differentiates it from other wayang